Phosphorylation of MtRopGEF2 by LYK3 mediates MtROP activity to regulate rhizobial infection in Medicago truncatula. Issue 10 (30th August 2021) - Wang, Mingxing; Feng, Huan; Xu, Peng; Xie, Qiujin; Gao, Jinpeng; Wang, Yanzhang; Zhang, Xiaowei; Yang, Jun; Murray, Jeremy D.; Sun, Fengli; Wang, Chunyan; Wang, Ertao; et al.
ABSTRACT: The formation of nitrogen‐fixing no dules on legume roots requires the coordination of infection by rhizobia at the root epidermis with the initiation of cell divisions in the root cortex. During infection, rhizobia attach to the tip of elongating root hairs which then curl to entrap the rhizobia. However, the mechanism of root hair deformation and curling in response to symbiotic signals is still elusive. Here, we found that small GTPases (MtRac1/MtROP9 and its homologs) are required for root hair development and rhizobial infection in Medicago truncatula . Our results show that the Nod factor receptor LYK3 phosphorylates the guanine nucleotide exchange factor MtRopGEF2 at S73 which is critical for the polar growth of root hairs. In turn, phosphorylated MtRopGEF2 can activate MtRac1. Activated MtRac1 was found to localize at the tips of root hairs and to strongly interact with LYK3 and NFP. Taken together, our results support the hypothesis that MtRac1, LYK3, and NFP form a polarly localized receptor complex that regulates root hair deformation during rhizobial infection. Abstract : The small GTPase MtRac1 is directly activated by symbiotic signals in Medicago truncatula . Phosphorylation of the guanine nucleotide exchange factor MtRopGEF2 by the Nod factor receptor LYK3 mediates MtRac1 activity to form a receptor complex that regulates root hair deformation and curling.